Service model under the lean approach and theory of constraints to increase the level of service in SMEs in the health sector - Ordoñez Silva, Ana Sofia (2022)
Companies in the health sector face the challenge of offering optimal patient care, knowing that they come to establishments with some pain or illness that afflicts them, thus hindering well-being during the care processes. The level of service represents around 16% of the annual costs of Peruvian SMEs in the health sector, analyzing the waiting time of patients, the quality of care received and the flow of people who come to the establishment according to capacity of this. Therefore, a model based on the Lean methodology and the theory of constraints was developed to improve the level of service. It was validated by carrying out a case study in a company in the sector located in the Peruvian province of Cañete. The results showed an increase in the level of service, improvement of workstations with the availability of necessary tools, reduction of cycle times from 5.1 hours to 1.2 hours, also reducing waiting times for office care from 1.81 hours at 0.35 hours.